Dyplomacja pałacowa Chin w Afryce .......... 71 - Kęsy, Wiktor; Duda, Miłosz (Oblicza dyplomacji, 2025)
CHINA’S “PALACE DIPLOMACY” IN AFRICAThe purpose of this paper is to provide an overview of the phenomena involved in building Chinese influence on the African continent. Particular attention has been paid to the modus operandi of the Chinese side, collectively referred to as “palace diplomacy”. The work includes references to investments made by China on the territory of African countries, as well as their translation into the political sphere. Largely these are ventures such as the construction of parliaments, headquarters of international organizations, government buildings, but also private residences of rulers, often very grand, hence the name palace diplomacy. The paper aimed to fill a gap in the discourse on Chinese activity and investment in Africa, as it often focuses on infrastructure investment, especially in transportation, while overlooking government or telecommunications infrastructure.